(untitled) (Conferencea, 2022)
. In the current economic conditions, when there is a decline in the economy of our country, a special role is played by increasing the innovative potential of industrial enterprises. The innovative potential of an enterprise is understood as a set of various types of resources that are necessary for the implementation of the main areas of innovative activity of an enterprise. Innovative potential can be viewed from various points of view, first of all, as a result of the innovative opportunity already available to the enterprise, and also as a product actually created at this enterprise. Today, there is an urgent need to improve the efficiency and improve the structure of Russian industry, which requires a significant increase in the level of competitiveness of domestic enterprises. In order to form the innovative potential of the enterprise, management must carry out a significant amount of work. At the same time, the presence of personnel resistance to various kinds of changes and innovations is often noted.